The Management of Facilities and Infrastructures in Educational Institution - Nurmayuli, Nurmayuli (Institut Agama Islam Negeri Lhokseumawe, 2022)
Educational institutions own equipment and resources called facilities and infrastructure that facilitate the delivery of educational services. Infrastructure management is required for successful infrastructure. Inventory is one of the key components of infrastructure management. It involves several steps, including management, implementation, organization, recording, and registration of inventory items. The study employs a qualitative paradigm and literary analysis methods. Primary books and scholarly publications comprising 40 references are used as research sources. The findings indicated that maintaining infrastructure quality and quantity is a goal of the invention focus. Activities involving inventory are fundamentally a continuous process. Additionally, the inventory of educational institutions provides data on the number, quality, wealth, planning, acquisition, and removal of facilities and infrastructure, as well as data on data accountability. Activities related to inventory include tracking purchases and creating reports.